2016
DOI: 10.3345/kjp.2016.59.9.355
|View full text |Cite
|
Sign up to set email alerts
|

Effects of early menarche on physical and psychosocial health problems in adolescent girls and adult women

Abstract: The menarcheal age of Korean women has been rapidly decreasing for the last 50 years, and the average menarcheal age of women born in the 1990s is approaching 12.6 years. In addition, interest in early puberty has been increasing recently owing to the rapid increase in precocious puberty. Generally, out of concern for short stature and early menarche, idiopathic central precocious puberty in female adolescents is treated with gonadotropin-releasing hormone analogs. Studies to date have described the associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 37 publications
1
32
0
3
Order By: Relevance
“…CPP disproportionately affects girls compared to boys; the mechanisms leading to these differences are unknown (24). Understanding more common causes of CPP, including genetic etiologies, is vital given that CPP has important short-and longterm implications for women, including increased risk of psychosocial distress, short stature, obesity, cardiovascular disease and type 2 diabetes in adulthood (25).…”
Section: Central Precocious Pubertymentioning
confidence: 99%
“…CPP disproportionately affects girls compared to boys; the mechanisms leading to these differences are unknown (24). Understanding more common causes of CPP, including genetic etiologies, is vital given that CPP has important short-and longterm implications for women, including increased risk of psychosocial distress, short stature, obesity, cardiovascular disease and type 2 diabetes in adulthood (25).…”
Section: Central Precocious Pubertymentioning
confidence: 99%
“…As such, menarche occurring prior to age 12 is considered early and from 14 years onwards is considered late (Karapanou & Papadimitriou, 2010; Marino et al., 2013; Wijnhoven et al., 2006). The onset and timing of menarche, early or late, appears to be associated with lifelong adverse health and social outcomes (Aegidius et al., 2011; Karapanou & Papadimitriou, 2010; Kvalheim et al., 2016; Le‐Ha et al., 2018; Mishra et al., 2009; Yoo, 2016). Early menarche shares a relationship with a number of diseases including higher risk of breast and endometrial cancers, obesity, diabetes, cardiovascular disease and menstrual/reproductive disorders (Aegidius et al., 2011; Karapanou & Papadimitriou, 2010; Kvalheim et al., 2016; Le‐Ha et al., 2018; Mishra et al., 2009; Yoo, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Obesity influences the onset of puberty as gonadal function is regulated by metabolic status. Insulin and leptin indirectly impinge hypothalamic neurons emitting gonadotropin-releasing hormone, a hierarchical hormone within the hypothalamic-pituitary-gonadal (HPG) axis [129,130]. As the prevalence of childhood obesity has increased, a study found that the median age at menarche decreased by 3-5.5 months in the US between the late 1960s and 1990 [8].…”
Section: Reproductive Healthmentioning
confidence: 99%